Erosion of universal health coverage and trend in the frequency of physician consultations in Spain - Lourdes Lostao; Elena Ronda; Cruz Pascual; Lucía Cea-Soriano; Almudena Moreno; Enrique Regidor (BMC, 2020)
Abstract Background We studied the frequency of physician visits in the native and immigrant populations in Spain before and after implementation of a governmental measure to restrict the use of public healthcare services by undocumented immigrants beginning in 2012. Methods Data were taken from the 2009 and 2014 European Health Surveys carried out in Spain. We investigated any physician consultation in the last 4 weeks before the interview, as well as visits to a family physician, public specialist physician and private specialist physician. We estimated the frequency of visits in 2009 and in 2014 in the native and immigrant populations and the difference in the frequency between the two populations, by calculating the percentage ratio estimated by binomial regression and adjusted for different confounders that are indicators of the need for assistance. Results The percentage of persons who consulted any physician in 2009 and 2014 was 31.7 and 32.9% in the native population, and 25.6 and 30.1% in the immigrant population, respectively. In the immigrant population, the frequency of visits to the general practitioner and public specialist physician increased, whereas in the native population only public specialist physician visits increased. The frequency of private specialist visits remained stable in both populations. After adjusting for the indicators of need for healthcare, no significant differences between the immigrant and native populations were seen in the frequency of visits, except for private specialist consultations, which were less frequent among immigrants. Conclusion The restriction of universal healthcare coverage in Spain did not reduce the frequency of physician visits between 2009 and 2014, as the frequency of these consultations was seen to increase in both the native and immigrant populations.